To solve this problem, we must simplify the the equation:
<span>Here is the base equation -2m - 5m - 8 = 3 + (-7) + m (Add all like terms):
</span>#1 -2m - 5m - 8 = 3 + (-7) + m (Property of Addition)<span>
#2 -7m - 8 = -4 + m (Most Simplified Equation)
The answer your would be the 2nd one. </span>-7m - 8 = m - 4
<span>
If I helped you out, please give me a gold crown. :)
</span>
Answer:
a 1/ (6^2)
Step-by-step explanation:
6^3 / 6^6
when dividing exponents we can subtract
6^ (3-6)
6^(-3)
negative exponents go from the numerator to the denominator
1/ (6^3) = 1/216 = 6^-3
1/6^2 is not equal
Answer:
2,2,2
Step-by-step explanation:
mode in my study is termed as highest occurrence
Answer:
8 units squared
Step-by-step explanation:
Answer:
Is this a question or..........
Step-by-step explanation: